2017
DOI: 10.7324/japs.2017.70923
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Physico-Chemical Parameters for Hyper Keratinase Production from a Newly Isolated Aspergillus sp. DHE7 using Chicken Feather as Substrate- Management of Biowaste

Abstract: Keratinases have recently gained biotechnological impetus due to their ability in degrading insoluble keratinous solid wastes into simplified forms, which used in the preparation of nitrogenous fertilizers, biodegradable films, glues and foils. Keratinases are widespread in nature and mainly produced by diverse microorganisms including bacteria, fungi and actinomycetes. Therefore, the aim of the present work was to isolate and identify a new potent fungal strain possessing extracellular keratinase production c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Keratinophilic fungi involve a large number of taxa belonging to several orders, families, and genera, including mainly dermatophytes and some saprophytic fungi, such as some species of Arthrodermataceae and Onygenaceae in the order Onygenales ( 10 ) and some members of the genera Geomyces and Pseudogymnoascus in the order Thelebolales ( 11 ). In addition, they contain a large number of common taxa, such as some species of the genera Aspergillus , Penicillium , and Trichoderma ( 12 , 13 ). In the years since we investigated the members of keratin-degrading fungal communities in Chinese soils, several new taxa have been identified and reported ( 14 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Keratinophilic fungi involve a large number of taxa belonging to several orders, families, and genera, including mainly dermatophytes and some saprophytic fungi, such as some species of Arthrodermataceae and Onygenaceae in the order Onygenales ( 10 ) and some members of the genera Geomyces and Pseudogymnoascus in the order Thelebolales ( 11 ). In addition, they contain a large number of common taxa, such as some species of the genera Aspergillus , Penicillium , and Trichoderma ( 12 , 13 ). In the years since we investigated the members of keratin-degrading fungal communities in Chinese soils, several new taxa have been identified and reported ( 14 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of keratinase and protease activity occurs at different temperatures and pH, as well as with different amounts of feather waste. Considering the effect of the concentration of chicken feather waste on the increased release of keratinolytic and proteolytic enzymes, El-Ghonemy and Ali [ 57 ] showed that higher production of keratinase and protease by the Aspergillus sp. strain DHE 7 was favored by increased native feather keratin concentration (2%).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a further increase in feather concentration to 3, 4, and 5% inhibited keratinase activity, but not the release of soluble proteins and peptides. It is possible, as El-Ghonemy and Ali [ 57 ] assumed, that this effect was related to the activity of fungal proteases. As opposed to keratinases, whose secretion is induced by the presence of a substrate, proteases belong to constitutional enzymes and their secretion is induced by nutritional stress, i.e., the lack of carbon, nitrogen, and energy sources [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation